2016
DOI: 10.5430/jer.v2n2p56
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of provider breastfeeding encouragement timing: Evidence from a large population-based study

Abstract: Background: Exclusive breastfeeding is the healthiest and most economical form of infant nutrition. Although research has indicated that professional support increases the length of time women breastfeed, the optimal timing of provider encouragement to sustain mothers' breastfeeding is unknown. We evaluated the impact of the timing of provider encouragement on breastfeeding initiation and three-month duration, especially among racial/ethnic minority mothers who have been underrepresented in breastfeeding outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Our results are consistent with findings from researchers who previously found that patients value provider breastfeeding recommendations (Chao et al, 2016; Dattilo et al, 2020; Wallenborn et al, 2018). A systematic review and meta-analysis by Kim et al (2018) supported the need for integrated programs for breastfeeding support that include provider training, interventions conducted from the pre- to postnatal period, connections between hospital and community, and involvement of healthcare professionals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with findings from researchers who previously found that patients value provider breastfeeding recommendations (Chao et al, 2016; Dattilo et al, 2020; Wallenborn et al, 2018). A systematic review and meta-analysis by Kim et al (2018) supported the need for integrated programs for breastfeeding support that include provider training, interventions conducted from the pre- to postnatal period, connections between hospital and community, and involvement of healthcare professionals.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with findings from researchers who previously found that patients value provider breastfeeding recommendations (Chao et al, 2016;Dattilo et al, 2020;Wallenborn et al, 2018). A systematic review and meta-analysis by Kim et al (2018) supported the need for Note.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Breastfeeding initiation is amenable to intervention. The optimal timing of intervention by health care providers may be the birth hospitalization, especially for populations least likely to breastfeed (Chao, Goldfinger, Gozalians, Sun, & Thaker, 2016). As the health care providers who take the lead on breastfeeding support during in-hospital births, nurses can serve as important facilitators or barriers to breastfeeding initiation (CDC, 2015).…”
Section: Promoting Breastfeeding Initiation Through Interventionmentioning
confidence: 99%